2016
DOI: 10.1136/bjophthalmol-2015-307375
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity loss in patients with age-related macular degeneration measured using a novel high-pass letter chart

Abstract: VA measurements with the MAC chart appear to be more sensitive to functional loss in AMD compared with conventional letter charts, with similar TRV. Simulations indicate this may be because the high-pass filtered letters are more vulnerable to undersampling as a result of retinal cell loss in the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 38 publications
(39 reference statements)
5
34
0
Order By: Relevance
“…The role of vanishing optotypes is potentially of further interest; vanishing optotypes have lower testretest variability (Shah et al, 2014) and may be particularly sensitive for detecting macular pathology (Shah et al, 2016). Starting with enclosed shapes and intentionally limiting acute angles and internal lines reduced the presence of high contrast regions that can arise in vanishing Sloan letters (e.g., at line endings or junctions), further reducing interoptotype variability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of vanishing optotypes is potentially of further interest; vanishing optotypes have lower testretest variability (Shah et al, 2014) and may be particularly sensitive for detecting macular pathology (Shah et al, 2016). Starting with enclosed shapes and intentionally limiting acute angles and internal lines reduced the presence of high contrast regions that can arise in vanishing Sloan letters (e.g., at line endings or junctions), further reducing interoptotype variability.…”
Section: Discussionmentioning
confidence: 99%
“…This feature of the proposed optotype set is an additional advantage over other well designed pictogram sets (for example Lea symbols [Hyvarinen et al, 1980] and the newly designed Kay pictures [Milling et al, 2016]), adding a level of flexibility to the type of testing which can be done. For example, since vanishing optotypes may be helpful for monitoring visual loss arising from macular degeneration (Shah et al, 2016), having a set of 10 vanishing optotypes that do not rely on the familiarity with Roman letters could be useful in a culturally diverse clinical setting. Whether there is an appropriate clinical application of vanishing optotypes for children is less well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shah et al[28] have developed a new set of optotypes for measuring visual acuity that consist of pseudo high-pass letters. The authors have demonstrated that the new optotypes have better test-retest variability than traditional optotypes, and recent evidence suggests that they are more sensitive to vision loss in early AMD to iAMD [29]. …”
Section: Resultsmentioning
confidence: 99%